2010
DOI: 10.1177/1466138110370496
|View full text |Cite
|
Sign up to set email alerts
|

Contacts and contracts: Economic embeddedness and ethnic stratification in London’s construction market

Abstract: Debates over the constitution and operation of economic markets tend to neglect their empirical variability and frequently fail to recognize the specific qualities of labour and contract markets. Based on one year’s participant observation on a London construction site in 2003/4, this article demonstrates how labour and contract markets were informally regulated and reproduced, characterized by alternative exchange forms that sometimes involved illegitimate practices. Chains of informal social networks, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Caplan 2007;Clarke 2006;Green 2011;Ness 2010;Sage, Brookes and Dainty 2010;Thiel 2010;Watts 2007). These studies develop critiques of problems not just identified by the industry itself (Murray and Langford 2003), but also government initiatives (e.g.…”
Section: Problematizing Constructionmentioning
confidence: 99%
See 4 more Smart Citations
“…Caplan 2007;Clarke 2006;Green 2011;Ness 2010;Sage, Brookes and Dainty 2010;Thiel 2010;Watts 2007). These studies develop critiques of problems not just identified by the industry itself (Murray and Langford 2003), but also government initiatives (e.g.…”
Section: Problematizing Constructionmentioning
confidence: 99%
“…Structural fragmentation has increased rapidly since the 1970s, as the UK's construction workforce has increasingly become casualized, evidenced by a strong rise in self-employment and labour only subcontracting (Clarke 2006;Green and May 2003;Green et al 2008;Winch 1998): in 1977 self-employed labour accounted for 30 per cent of the UK construction workforce; by 1995 this figure had risen to 60 per cent (Green and May 2003: 102). The mutually reinforcing fragmentation and casualization of the UK construction industry was politically encouraged: the 1979 -1997 Conservative governments promoted labour deregulation ostensibly to provide large construction firms with greater labour flexibility to protect themselves against unpredictable workloads, partly caused by the exposure of the industry to economic downturns as well as the vagaries of the British weather (Dainty, Bagilhole and Green 2007b;Green 2006;Green and May 2003;Harvey 2003;Thiel 2010;Winch 1998). For some, such policies belie a far more insidious purpose: large firms benefit from a fragmented/casualized workforce by avoiding costs related to employment rights (pensions, sick-pay, notice periods, redundancy payments, training, diversity policies, accountability, etc.)…”
Section: Problematizing Constructionmentioning
confidence: 99%
See 3 more Smart Citations